2020
DOI: 10.1007/s40843-020-1458-5
|View full text |Cite
|
Sign up to set email alerts
|

Non-noble metal single-atom catalyst of Co1/MXene (Mo2CS2) for CO oxidation

Abstract: MXene is a variety of new two-dimensional (2D) materials with early transition metal carbides, nitrides, and carbonitrides. Quantum chemical studies have been carried out on the geometries, electronic structures, stability and catalytic properties of a non-noble metal single-atom catalyst (SAC) with single Co atom anchored on MXene materials of Mo 2 CS 2. The Co adatom anchored on top of the Mo atom of this MXene is found to be rather stable, and this SAC is appropriate for CO oxidation. The charge transfers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 99 publications
2
31
0
Order By: Relevance
“…It is found that the S atom structure of the bridge site will migrate to the hcp site after optimization, for the Mo 2 CS 2 of the hcp site has the lowest total energy and the most stable structure, which is consistent with the calculation results of Talib et al. [59] . In order to avoid the interaction between adjacent CO 2 caused by periodicity, a 3×3 Mo 2 CS 2 supercell is used in this article to anchor TM atoms.…”
Section: Introductionsupporting
confidence: 82%
“…It is found that the S atom structure of the bridge site will migrate to the hcp site after optimization, for the Mo 2 CS 2 of the hcp site has the lowest total energy and the most stable structure, which is consistent with the calculation results of Talib et al. [59] . In order to avoid the interaction between adjacent CO 2 caused by periodicity, a 3×3 Mo 2 CS 2 supercell is used in this article to anchor TM atoms.…”
Section: Introductionsupporting
confidence: 82%
“…Among many other competing 2D materials, MXene sheets with large active sites, highly hydrophilic surface, good charge transfer kinetics, high electrical conductivity, and good structural stability provide polished qualities to become efficient catalysts. [ 42–45 ] MXenes are the newly emerging family of 2D TM carbides and nitrides with the general formula M n +1 X n T m ( n = 1–4), where M represents early TMs, X = C and/or N element and T represents the surface functional groups such as OH, O and, F. Recently, the family of MXenes has been expanded to include the ordered double‐TM carbides M 2 M ′ C 2 and M 2 M 2 ′ C 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, MXenes composed with transition metal carbides, carbonitrides and nitrides [68], as a new type of multiatomic-layer 2D nanomaterial, have received a lot of attention both theoretically and experimentally because of their versatile applications in energy storage, catalysis, sensors, flexible functional materials, etc. [32,[69][70][71][72][73][74][75][76]. The general formula of MXene is denoted as M n+1 X n T x (n = 1-4) [68,[77][78][79], where M is an early transition metal (Ti, V, Cr, Nb, Mo, etc.…”
Section: Introductionmentioning
confidence: 99%